Comparison of beta-kurtosis and kurtosis methods for troubleshooting the performance of a transmission vehicle using vibrating frequencies - Dadkhah Laleh, Alireza; Ettefagh, Mirmohammad; Hasanezhad Qadim, Reza (International Journal of Engineering and Technology, 2018)
One of the main methods in maintenance and repair is a preventive maintenance method that is often more effective. The requirements of this method are to monitor the performance of machinery during operation. One of the car's functions that is monitored in this way is its vibra-tions. In this paper, a mathematical model of vibration analysis of a passenger car gearbox is presented based on Beta-Kurtosis and Kurtosis methods. In the next step, the data and test settings for the gearbox are based on the accelerometer installation to record the vibrations of the gearbox. To verify the accuracy of the proposed method, the results of the vibrational analysis of the car gearbox in four modes of a healthy gearbox, defective gearbox in the shaft end bearing, gear shaft failure on the gear shaft, simultaneous failure of the bearing and gearbox on the gear shaft were compared. Also, the results are compared for both Kurtosis and Beta-Kurtosis methods. The results show that both of the proposed methods are very accurate in identifying faults in the gearbox and determining the type of fault.Â Â
Keywords: Gearbox; Troubleshooting; Beta-Kurtosis; Kurtosis; Vibrational Frequency Analysis